2019
DOI: 10.3389/fphys.2019.00676
|View full text |Cite
|
Sign up to set email alerts
|

Long-Chain Fatty Acid Receptors Mediate Relaxation of the Porcine Lower Esophageal Sphincter

Abstract: Long-chain fatty acids activate the free fatty acid receptor 1 (FFA1) and FFA4. In the gastrointestinal system, FFA1 and FFA4 have been found in the pancreas and intestine. Fatty food and decreased lower esophageal sphincter (LES) motility are associated with gastroesophageal reflux disease. The effect of long-chain fatty acids on the esophageal motility is unknown. The purpose of this study is to investigate the effects of long-chain fatty acids on the porcine LES motility ex vivo using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
3
0
0
Order By: Relevance
“…Interestingly, no correlation was observed between the FFAR expression and patients’ perception of the symptoms, regardless of the disease subtype. The results we obtained correspond with the study of Tsai et al [ 24 ], showing that the selective agonists of FFAR1 (fasiglifam, TUG424) induce the relaxation of porcine LES strips ex vivo in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Interestingly, no correlation was observed between the FFAR expression and patients’ perception of the symptoms, regardless of the disease subtype. The results we obtained correspond with the study of Tsai et al [ 24 ], showing that the selective agonists of FFAR1 (fasiglifam, TUG424) induce the relaxation of porcine LES strips ex vivo in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 91%
“…The results we obtained correspond with the study of Tsai et al [24], showing that the selective agonists of FFAR1 (fasiglifam, TUG424) induce the relaxation of porcine LES strips ex vivo in a dose-dependent manner. Interestingly, similarly to Tsai et al [24], we observed a low expression of FFAR4 in esophageal samples. In line with our observations, they found that FFAR4 agonists (GW9508 and GSK137647) were less potent in relaxing the LES than those of FFAR1.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation